Peranan Advokat sebagai Mediator di Pengadilan Agama Perkara Perceraian Menurut Maqashid Al-Syariah - Hajijah Rizkinami Siregar; Aulia Nur Anjani Lubis; Fatimah Zahara (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Rarely do we find win-win cases at this time, even though the judiciary is a case breaker, as well as a settlement of cases. One solution to resolving cases in religious courts in divorce cases is based on the concept of win-win, the difference between sharia advocates and non-shariah advocates is when they provide defense, assistance, and become the power of attorney for and on behalf of their clients sharia advocates based on the principle of mutual help, as well as sticking to his beliefs, namely the teachings of Islam, an advocate who acts as a mediation in divorce cases is better left to a competent advocate, namely a sharia advocate because sharia advocates themselves are guided by Islamic teachings by always carrying out their profession properly in accordance with religious directives Islam (maqashid sharia). Meanwhile, based on the task, there is no difference between sharia advocates and non-sharia advocates, namely defending the interests of society and its clients in upholding justice. Keywords: Advocates, Mediators, Maqasid al-syariah.